CSR DISCLOSURE AND FIRM VALUE: A STUDY ON GCC ISLAMIC BANKS - Muhamad Fikri Aziz; Razli Ramli; Mohd Shukor Harun (Journal of Islamic, Social, Economics and Development, 2023)
This study explores the CSR disclosure practices of the Islamic banks in the Gulf Cooperation Council (GCC) countries during the period 2016 - 2020 and examines its effects on firm value. Based on Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) Governance Standard No. 7 guidelines and using content analysis, the paper develops a comprehensive CSR Disclosure index for GCC Islamic banks. The study applies the ordinary least squares regression analysis for the hypothesis testing and for finding its effect of respective dependent variables. The results show a very low level of CSR disclosure among the sample Islamic banks in GCC countries. For the economic consequences of CSR disclosure, the study documents an inverse performance effect of CSR Disclosure while board size, board composition and CEO duality indicate significant positive effects on firm value. The relatively small sample size of GCC Islamic banks may limit the application of the findings to other Islamic Financial Institutions such as Takaful and the Islamic Unit Trust Company. The findings of this study initiate the global debate on the need for corporate governance reform in Islamic banks by providing insights on the role played by corporate governance mechanisms in encouraging and enhancing CSR disclosure practices among Islamic banks. The findings also have important implications for investors, managers, regulatory bodies, policy makers and Islamic banks in the GCC countries. The results of the study do not support the idea that Islamic banks operating on Islamic principles can meet their social responsibilities through promoting CSR activities and by differentiating themselves from non-Islamic banks. This is the first study to examine the CSR disclosure in GCC Islamic banks using comprehensive CSR disclosure and corporate governance variables and, therefore, adds value to the existing CSR literature in banking.